Disorders Causing Secondary Hypertension in Patients Less Than 45 Years of Age - Gilani, Sayed Tanveer Abbas; Iftikhar, Ghazala; Latif, Sobia; Ahmed, Bilal; Bokhari, Syed Aown Shah; Bukhari, Airas (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of disorders causing secondary hypertension in patients less than 45 years of age.Study Design: Cross-sectional study.Place and Duration of Study: Department of Pathology and Medicine, Combined Military Hospital (CMH), Risalpur, Pakistan, along with Armed Forces Institute of Pathology (AFIP)and Pak Emirates Military Hospital (PEMH) Rawalpindi, Pakistan from Apr 2017 to Apr 2019.Methodology: A total of 50 patients, less than 45 years of age, newly diagnosed with hypertension (systolic blood pres-sure>140 mm Hg or diastolic BP>90 mm Hg) and reported to CMH Risalpur for the workup of HTN were included. Analysis of serum cholesterol, triglycerides, urea, creatinine, sodium, potassium, calcium, thyroid stimulating hormone, plasma glucose random, urine analysis and renal ultrasonography were carried out. In addition, serum cortisol, 24 hours urinary free cortisol, dexamethasone suppression test, growth hormone level, insulin-like growth factor-1,24 hours urinary vanillylmandelic acid, serum aldosterone and renin levels, Doppler renal ultrasonography, renal arteriogram, CT abdomen, MRI pituitary and MR/CT angiography were carried out.Results: A total of 50 patients comprised of 82% males and 18% females with a mean age of 36.1±6.2years. Primary hypertension was in observed in 31(62%) cases. Secondary causes of HTN in 19(38%) cases, were obstructive sleep apnea (4, 8%), primary hyperaldosteronism (3,6%), renal parenchymal hypertension (3,6%), renal artery stenosis (1,2%), Cushing's syndrome (2,4%), hyperthyroidism (2,4%), hypothyroidism (2,4%), pheochromocytoma (1,2%) and coarctation of aorta (1,2%) cases.Conclusion: Obstructive sleep apnea primary hyper-aldosteronism and renal parenchymal diseases were the commonest.........